2013
DOI: 10.1242/jcs.127845
|View full text |Cite
|
Sign up to set email alerts
|

A novel PAR-1-binding protein, MTCL1, plays critical roles in organizing microtubules in polarizing epithelial cells

Abstract: SummaryThe establishment of epithelial polarity is tightly linked to the dramatic reorganization of microtubules (MTs) from a radial array to a vertical alignment of non-centrosomal MT bundles along the lateral membrane, and a meshwork under the apical and basal membranes. However, little is known about the underlying molecular mechanism of this polarity-dependent MT remodeling. The evolutionarily conserved cell polarity-regulating kinase PAR-1 (known as MARK in mammals), whose activity is essential for mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 38 publications
9
56
1
Order By: Relevance
“…These results suggest that MTCL1 has a role in mediating the association of MTs with the Golgi membrane. Moreover, the MTCL1 localization on acetylated MTs, sometimes observed in the regions lacking GM130 signals (a bracket in Fig.1c), is consistent with its MT-crosslinking activity we have previously demonstrated 15 . Analysis by super-resolution microscopy (G-STED) resolved the perinuclear tracks of acetylated MTs into finer MT strands and revealed that many MTCL1 signals were localized between them or at their intersection points (Fig.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…These results suggest that MTCL1 has a role in mediating the association of MTs with the Golgi membrane. Moreover, the MTCL1 localization on acetylated MTs, sometimes observed in the regions lacking GM130 signals (a bracket in Fig.1c), is consistent with its MT-crosslinking activity we have previously demonstrated 15 . Analysis by super-resolution microscopy (G-STED) resolved the perinuclear tracks of acetylated MTs into finer MT strands and revealed that many MTCL1 signals were localized between them or at their intersection points (Fig.…”
supporting
confidence: 88%
“…As we have reported previously 15 , MTCL1 has two MT-binding domains at the N-terminal and C-terminal regions, the latter termed the KR-rich region (KR; Fig. 6a).…”
mentioning
confidence: 73%
See 3 more Smart Citations